Spiral blurring correction with water–fat separation for magnetic resonance fingerprinting in the breast - Nolte, Teresa; Gross‐Weege, Nicolas; Doneva, Mariya; Koken, Peter; Elevelt, Aaldert; Truhn, Daniel; Kuhl, Christiane; Schulz, Volkmar (Magnetic resonance in medicine, 2020)
Purpose Magnetic resonance fingerprinting (MRF) with spiral readout enables rapid quantification of tissue relaxation times. However, it is prone to blurring because of off‐resonance effects. Hence, fat blurring into adjacent regions might prevent identification of small tumors by their quantitative T1 and T2 values. This study aims to correct for the blurring artifacts, thereby enabling fast quantitative mapping in the female breast. Methods The impact of fat blurring on spiral MRF results was first assessed by simulations. Then, MRF was combined with 3‐point Dixon water–fat separation and spiral blurring correction based on conjugate phase reconstruction. The approach was assessed in phantom experiments and compared to Cartesian reference measurements, namely inversion recovery (IR), multi‐echo spin echo (MESE), and Cartesian MRF, by normalized root‐mean‐square error (NRMSE) and SD calculations. Feasibility is further demonstrated in vivo for quantitative breast measurements of 6 healthy female volunteers, age range 24–31 y. Results In the phantom experiment, the blurring correction reduced the NRMSE per phantom vial on average from 16% to 8% for T1 and from 18% to 11% for T2 when comparing spiral MRF to IR/MESE sequences. When comparing to Cartesian MRF, the NRMSE reduced from 15% to 8% for T1 and from 12% to 7% for T2. Furthermore, SDs decreased. In vivo, the blurring correction removed fat bias on T1/T2 from a rim of ~7–8 mm width adjacent to fatty structures. Conclusion The blurring correction for spiral MRF yields improved quantitative maps in the presence of water and fat.